Images of Women in Abhijnanashakuntalam as Role Model for Women Empowerment - Khanal, Shyam (Haimaprabha, 2021)
This paper aims to oversee the forms and image of women in the play Abhijnanashakuntalam written by Kalidasa; a great poet in Sanskrit literature. It is found that most of his works represent two different aspects of woman, one in the form of the poetic and artistic depiction of woman and the other in the form of her status in the prevailing society. The women were able to inspire action and hero’s aspirations with her own nobility and deep human affection which is the typical image for female character and an endless source of inspiration for contemporary art and literature. Hence, the portrayal of women is with the outer and inner beauty in relation to social issues like religion, caste, marriage, sacrifice etc.